2009
DOI: 10.1007/s10508-009-9529-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Self-Reported Sexual Arousal on Responses to Sex-Related and Non-Sex-Related Disgust Cues

Abstract: Prior to and during sexual intercourse, people are exposed to stimuli that in other contexts might act as disgust-eliciting cues. This study examined whether sexual arousal, in contrast to general arousal, could selectively reduce reported disgust for cues that pilot participants identified as sex or non-sex related. Male undergraduates were randomly assigned to one of four viewing groups. One group viewed erotic female images, a second clad female images, a third pleasantly arousing images (e.g., skydiving), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 11 publications
7
80
2
Order By: Relevance
“…Perhaps, this was partly due to the strength of the sexual stimulation. Previous research has shown that both in men (Stevenson, Case & Oaten, 2011) and women (Borg & de Jong, 2012), sexual stimulation reduces the disgusting properties of sex-relevant disgust elicitors. Accordingly, also in the present study, sexual disgust may have been weakened or been taken away by the concurrently elicited sexual arousal.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, this was partly due to the strength of the sexual stimulation. Previous research has shown that both in men (Stevenson, Case & Oaten, 2011) and women (Borg & de Jong, 2012), sexual stimulation reduces the disgusting properties of sex-relevant disgust elicitors. Accordingly, also in the present study, sexual disgust may have been weakened or been taken away by the concurrently elicited sexual arousal.…”
Section: Discussionmentioning
confidence: 99%
“…[44] Women who are sexually aroused report less disgust toward pathogen cues and behaviorally avoid cues to pathogens less (see also [45][46][47][48]) Kinship…”
Section: Information Integrated With Pathogen Indexmentioning
confidence: 99%
“…Previous studies have indicated an association between disgust and sexual arousal (de Jong et al, 2010; Stevenson et al, 2011; Borg and de Jong, 2012; Lee et al, 2014; Grauvogl et al, 2015). Among men, high levels of trait pathogen disgust sensitivity predicted higher levels of genital and subjective sexual arousal (Lee et al, 2014; Grauvogl et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…This result was also consistent with Al-Shawaf's study that found that individuals who preferred short-term mating tended to exhibit low levels of sexual disgust (Al-Shawaf et al, 2015). Others have also reported that sex-related disgust was associated with risky sexual behavior (Stevenson et al, 2011); thus, having multiple sexual partners should increase the likelihood of sexually transmitted infection and trigger cues related to sexual disgust. Therefore, suppressed level of sexual disgust sensitivity is likely to play an important role in the behavior of men's multiple sexual partners.…”
Section: Discussionmentioning
confidence: 99%